Hollow TiO2-based photocatalytic composite material for degrading rhodamine B and preparation method thereof

By modifying the photosensitizer on the surface of the hollow TiO2 microspheres and covering the hydrophobic crosslinker layer, an efficient TiO2-based photocatalytic composite material was prepared, which solved the problems of low degradation efficiency and poor solid-liquid separation efficiency of existing TiO2-based photocatalysts, and achieved efficient degradation of rhodamine B and good recycling life.

CN119608236AActive Publication Date: 2025-03-14TAIYUAN UNIVERSITY OF TECHNOLOGY +1
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411782836.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-14
Estimated Expiration
2044-12-06

AI Technical Summary

Technical Problem

The catalytic degradation efficiency of existing TiO2-based photocatalysts in the degradation of rhodamine B is not high, the solid-liquid separation efficiency is low, and the circulation life is poor.

Method used

By modifying the aniline compound photosensitizer on the surface of anatase-type hollow TiO2 microspheres and coating the acrylate-based hydrophobic crosslinker polymer layer, a TiO2-based photocatalytic composite material with switchable surface wetting was prepared.

Benefits of technology

The catalytic degradation efficiency, solid-liquid separation efficiency and recycling service life are significantly improved, and the degradation rate of rhodamine B of the material reaches 92%, and it maintains high efficiency performance during multiple recycling and use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119608236A_ABST
    Figure CN119608236A_ABST
Patent Text Reader

Abstract

The invention relates to a hollow TiO2-based photocatalytic composite material for degrading rhodamine B and a preparation method of the hollow TiO2-based photocatalytic composite material. Anatase type hollow TiO2 microspheres are used as a catalytic matrix, the surface of the anatase type hollow TiO2 microspheres is modified with an aniline compound photosensitizer, a hydrophobic cross-linking agent polymer layer formed by taking an acrylate hydrophobic cross-linking agent as a raw material is coated, and the hollow TiO2-based photocatalytic composite material for degrading rhodamine B is obtained. The brand-new hollow TiO2-based photocatalytic composite material is obtained, and the problems that an existing TiO2-based photocatalyst is low in rhodamine B degradation catalytic efficiency, low in solid-liquid separation efficiency and short in cycle service life are effectively solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of photocatalytic degradation materials, and relates to a photocatalytic material for degrading dye Rhodamine B in waste water, in particular to a photocatalytic composite material based on hollow TiO2 microspheres. Background Art

[0002] Rhodamine B is a catechol-based cationic alkaline dye with a strong fluorescence effect. Its concentration in printing and dyeing wastewater can be as high as 100 ppm and it is difficult to degrade. Therefore, it is necessary to efficiently remove the organic pollutant Rhodamine B in wastewater.

[0003] In recent years, various degradation methods such as electrolysis, adsorption, extraction, electrochemical oxidation and photocatalysis have been applied to the treatment of dye wastewater. Among them, photocatalytic degradation technology, as one of the most effective methods, can effectively degrade rhodamine B, with the characteristics of low energy consumption, high efficiency and no secondary pollution. TiO2-based photocatalytic materials with good photocatalytic activity, high conversion efficiency and long-lasting catalytic effect have attracted much attention.

[0004] Phongamwong et al. (Applied Catalysis B-Environment and Energy, 2022, 325:122336.) Using Au 25 Clusters, Au nanoparticles and chlorophyll were used to functionalize anatase / rutile mixed phase TiO2 to prepare nanophotocatalysts. The modified TiO2 catalyst achieved a 100% degradation efficiency for Rhodamine B within 60 minutes. Chen et al. (Environmental Research, 2023, 232: 116311.) prepared a carbon / fluorine co-doped TiO2 photocatalyst C / F-Ag-TiO2 with surface-deposited silver by a hydrothermal method, and the degradation rate of Rhodamine B reached 84.2% within 4 hours.

[0005] However, the catalytic degradation efficiency of these existing TiO2-based photocatalysts during the degradation process is not high enough, especially due to the high affinity of the catalyst to the aqueous phase system, resulting in low solid-liquid separation efficiency of the catalyst after degradation and poor cycle life of the catalyst.

[0006] By modifying the surface of anatase-type hollow TiO2 microspheres with a photosensitizer and coating them with a hydrophobic crosslinker polymer layer, a surface wettability-switchable TiO2-based photocatalytic material with high catalytic activity, high catalytic stability and high solid-liquid separation efficiency is obtained. This material has good research and development value and application potential for improving the degradation efficiency, solid-liquid separation efficiency and cycle life of TiO2-based photocatalysts used for the degradation of Rhodamine B in wastewater. Summary of the invention

[0007] The purpose of the present invention is to provide a hollow TiO2-based photocatalytic composite material for degrading Rhodamine B and a preparation method thereof, so as to effectively improve the problems of low catalytic efficiency, low solid-liquid separation efficiency and poor cycle life of existing TiO2-based photocatalysts for degrading Rhodamine B.

[0008] To achieve the above-mentioned purpose of the invention, the present invention uses anatase-type hollow TiO2 microspheres as a catalytic matrix, modifies the surface of the microspheres with an aniline compound photosensitizer, and coats them with a hydrophobic crosslinker polymer layer formed with an acrylate hydrophobic crosslinker as a raw material, thereby preparing a new hollow TiO2-based photocatalytic composite material.

[0009] First, the hollow TiO2-based photocatalytic composite material of the present invention uses anatase-type hollow TiO2 microspheres as a catalytic matrix. The spherical morphology of the hollow TiO2 microspheres gives them a larger specific surface area, and the hollow structure gives them a lower density, thereby giving them a lower refractive index and expansion coefficient and a stronger light absorption capacity. More importantly, under ultraviolet light irradiation, the surface valence band electrons of the hollow TiO2 microspheres are excited to the conduction band, and the electrons and holes migrate to the H-TiO2 surface, causing a change in the surface chemical polarity, which can improve its surface hydrophilicity and photocatalytic efficiency.

[0010] Secondly, the hollow TiO2-based photocatalytic composite material of the present invention uses aniline compounds as photosensitizers, and the photosensitizers are modified on the surface of the hollow TiO2 microspheres, which not only does not affect the internal crystal structure of TiO2, but also promotes light-induced charge separation and improves the recombination of photogenerated electron-hole pairs, thereby improving the catalytic degradation efficiency of the overall hollow TiO2-based photocatalytic composite material.

[0011] Third, the outer layer of the hollow TiO2-based photocatalytic composite material described in the present invention is a hydrophobic crosslinker polymer layer, which can be promoted to form a three-dimensional network hydrophobic polymer outer layer through a hydrothermal method. The hydrophobic outer layer and the inner layer of photo-induced hydrophilic hollow TiO2 microspheres act synergistically, so that the composite material as a whole can achieve surface wettability hydrophilic / hydrophobic switching under ultraviolet light / dark conditions, thereby improving the solid-liquid separation efficiency and cycle life of the composite material.

[0012] Furthermore, the present invention also provides a method for preparing a suitable hollow TiO2-based photocatalytic composite material for degrading rhodamine B, comprising: modifying the hollow TiO2 microspheres by silanization with a silane coupling agent to obtain silylated hollow TiO2 microspheres, adding an aniline compound photosensitizer, an acrylate hydrophobic cross-linking agent and an initiator to a toluene solvent system, and performing an in-situ hydrothermal reaction under an inert atmosphere to form a three-dimensional network-like hydrophobic cross-linked polymer layer coated on the surface of the hollow TiO2 microspheres, thereby obtaining the hollow TiO2-based photocatalytic composite material described in the present invention.

[0013] The present invention has no particular limitation on the hollow TiO2 microspheres used as the catalyst substrate, and hollow TiO2 microspheres prepared by various methods reported in the literature can be used.

[0014] However, preferably, the present invention selects to use anatase-type hollow TiO2 microspheres as the catalytic matrix of the hollow TiO2-based photocatalytic composite material.

[0015] Furthermore, the anatase hollow TiO2 microspheres described in the present invention are more preferably hollow TiO2 microspheres obtained by using carbon microspheres prepared by a hydrothermal method as a hard template, using butyl titanate to undergo a solvent thermal self-assembly reaction on the surface of the carbon microspheres, and calcining at a high temperature in an air atmosphere to remove the internal hard template carbon microspheres.

[0016] Likewise, the present invention has no particular limitation on the silane coupling agent for silanization modification, and it can be any conventionally used trimethoxysilane coupling agent, which serves to increase the surface activity of the hollow TiO2 microspheres to facilitate the subsequent grafting and coating of the hydrophobic cross-linked polymer layer.

[0017] Preferably, the present invention uses (3-mercaptopropyl)trimethoxysilane as a silane coupling agent, and its usage is preferably 4 to 8 times the mass of the hollow TiO2 microspheres.

[0018] Specifically, the present invention uses aniline compounds that can promote charge separation as photosensitizers. Preferably, the present invention uses o-phenylenediamine as photosensitizer, and its amount is 3 to 5 times the mass of the silanized hollow TiO2 microspheres.

[0019] The acrylate hydrophobic crosslinking agent described in the present invention can be any acrylate crosslinking agent that can undergo self-polymerization reaction under the action of an initiator to form a hydrophobic crosslinked polymer layer, such as trimethylolpropane-trimethacrylate, pentaerythritol triacrylate, ethyl methacrylate, etc. Its function is to form a hydrophobic crosslinked polymer coating layer on the surface of the silanized hollow TiO2 microspheres.

[0020] Furthermore, the present invention preferably uses trimethylolpropane-trimethacrylate as a hydrophobic crosslinking agent, and its amount is 20 to 55 times the mass of the silanized hollow TiO2 microspheres.

[0021] Furthermore, the initiator functions to initiate the self-polymerization of the acrylate hydrophobic crosslinker, and various conventional low-activity azo initiators can be used, including but not limited to 2,2′-azobis(2-methylpropionitrile), azobisisoheptanenitrile, etc., or conventional inorganic persulfate initiators can be used, including but not limited to ammonium persulfate, potassium persulfate, etc.

[0022] Furthermore, the present invention preferably uses 2,2′-azobis(2-methylpropionitrile) as the initiator, and the amount thereof is 0.3 to 0.7 times the mass of the silylated hollow TiO2.

[0023] Furthermore, the polymerization process of the in-situ hydrothermal reaction is carried out under an inert atmosphere and stirring conditions, the in-situ hydrothermal reaction temperature is preferably 60 to 80° C., and the reaction time is preferably 6 to 14 hours.

[0024] Furthermore, the reaction product is fully washed with anhydrous ethanol and deionized water, and then vacuum dried to finally obtain the hollow TiO2-based photocatalytic composite material of the present invention.

[0025] The hollow TiO2-based photocatalytic composite material described in the present invention is a dark brown-red powder material. Under the action of ultraviolet light, the surface is hydrophilic and can be fully dispersed in an aqueous solution containing rhodamine B to catalytically degrade rhodamine B, and exhibits strong light absorption ability and faster catalytic degradation efficiency. After the catalytic degradation is completed, the dispersion is placed in the dark, and the surface of the composite material will become hydrophobic, which is easy to fully settle and separate from the liquid phase, thereby achieving effective purification of the water body and recovery of the catalyst.

[0026] The hollow TiO2-based photocatalytic composite material of the present invention has strong catalytic degradation ability for Rhodamine B, high solid-liquid separation efficiency, and long cycle life. The material preparation method is simple, the cost is low, the operation is convenient, and the practicability is strong. It can be widely used in the fields of photocatalysis, degradation, water treatment, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 Field emission scanning electron microscope images of hollow TiO2 microspheres (a) and hollow TiO2-based photocatalytic composite materials (b).

[0028] Figure 2 The infrared spectra (a) and X-ray diffraction spectra (b) of hollow TiO2 microspheres and hollow TiO2-based photocatalytic composite materials.

[0029] Figure 3 The water contact angle of the hollow TiO2-based photocatalytic composite material changes with UV irradiation time (a) and the wettability switching performance under UV irradiation and dark conditions (b).

[0030] Figure 4 The ultraviolet absorbance of the aqueous solution changes with time (a) and the degradation curve (b) during the degradation of Rhodamine B by the hollow TiO2-based photocatalytic composite material.

[0031] Figure 5 The regeneration performance of hollow TiO2-based photocatalytic composite materials for degradation of Rhodamine B.

[0032] Figure 6 The ultraviolet absorbance of the aqueous solution changes with time during the degradation of Rhodamine B by hollow TiO2 microspheres (a) and the degradation curve (b).

[0033] Figure 7 The regeneration performance of hollow TiO2 microspheres in degrading rhodamine B.

[0034] Figure 8 The ultraviolet absorbance of the aqueous solution changes with time (a) and the degradation curve (b) during the degradation of Rhodamine B by the hollow TiO2-based photocatalytic composite material without photosensitizer. Implementation

[0035] The specific implementation of the present invention is further described in detail below in conjunction with the accompanying drawings and examples. The following examples are only used to more clearly illustrate the technical solution of the present invention so that those skilled in the art can well understand and utilize the present invention, rather than limiting the scope of protection of the present invention.

[0036] The production processes, experimental methods or detection methods involved in the embodiments of the present invention, unless otherwise specified, are all conventional methods in the prior art, and their names and / or abbreviations are all conventional names in the field, and are very clear and unambiguous in the relevant application fields. Technical personnel in the field can understand the conventional process steps based on the names and apply the corresponding equipment, and implement them according to conventional conditions or the conditions recommended by the manufacturer.

[0037] The various instruments, equipment, raw materials or reagents used in the embodiments of the present invention are not particularly limited in terms of their sources, and are all conventional products that can be purchased through regular commercial channels, or can be prepared according to conventional methods well known to those skilled in the art.

[0038] The present invention provides a method for preparing a hollow TiO2-based photocatalytic composite material, which specifically comprises: Using glucose as the carbon source, carbon microspheres as the hard template were prepared by conventional hydrothermal method, and butyl titanate was used as the titanium source and self-assembled on the surface of the carbon microspheres by solvothermal method to obtain a TiO2 core-shell structure composite containing hard template carbon microspheres. The internal hard template carbon microspheres were further calcined at high temperature to remove them, and hollow TiO2 microspheres were obtained after cooling.

[0039] The hollow TiO2 microspheres are silanized with a silane coupling agent, and then toluene is used as a solvent, and a photosensitizer, a hydrophobic cross-linking agent and an initiator are added. An in-situ hydrothermal reaction is carried out under an inert N2 atmosphere to coat the surface of the hollow TiO2 microspheres with a three-dimensional network-like hydrophobic cross-linked polymer layer. The washed product is centrifuged and dried to obtain the hollow TiO2-based photocatalytic composite material described in the present invention.

[0040] Among them, the present invention preferably uses (3-mercaptopropyl)trimethoxysilane as a silane coupling agent, and its amount is 4 to 8 times the mass of the hollow TiO2 microspheres.

[0041] Furthermore, in the in-situ hydrothermal reaction polymerization process described in the present invention, the hollow TiO2 microspheres, photosensitizer, hydrophobic crosslinking agent and initiator are indispensable.

[0042] Among them, preferably, the present invention uses o-phenylenediamine as a photosensitizer to promote charge separation, and its amount is 3 to 5 times the mass of the silanized hollow TiO2 microspheres.

[0043] Among them, the present invention preferably uses trimethylolpropane-trimethacrylate as the hydrophobic crosslinking agent, and its usage is 20 to 55 times the mass of the silanized hollow TiO2 microspheres.

[0044] Among them, the present invention preferably uses 2,2′-azobis(2-methylpropionitrile) as the initiator, and its dosage is 0.3 to 0.7 times the mass of the silanized hollow TiO2 microspheres. Its function is to initiate the self-polymerization of the hydrophobic cross-linking agent to form a three-dimensional network-like hydrophobic cross-linked polymer coating on the surface of the silanized hollow TiO2 microspheres.

[0045] Furthermore, the in-situ hydrothermal polymerization process must be carried out under N2 inert atmosphere and magnetic stirring conditions, the in-situ hydrothermal reaction temperature is preferably 60-80°C, and the reaction time is preferably 6-14h.

[0046] Furthermore, the present invention preferably uses anhydrous ethanol and deionized water to fully wash the reaction product, and after vacuum drying at 60° C. for 12 hours, the hollow TiO2-based photocatalytic composite material of the present invention is obtained. Example

[0047] Example 1

[0048] Weigh 4.95 g of glucose into a beaker containing 50 mL of deionized water, disperse it evenly by ultrasonic treatment at 25 °C for 2 min, transfer it to a polytetrafluoroethylene-lined reactor, seal it, and place it in an oven for hydrothermal reaction at 180 °C for 10 h.

[0049] After the reaction was completed, the reaction product was cooled to room temperature in the furnace, washed thoroughly with anhydrous ethanol and deionized water, dried under vacuum at 60° C. for 12 h, and fully ground to obtain carbon microspheres.

[0050] Measure 2 mL of butyl titanate and slowly add it into 20 mL of anhydrous ethanol at a rate of 1 drop per second. After the addition is completed, stir magnetically for 30 minutes.

[0051] Weigh 0.4 g of carbon microspheres as a hard template, add them to the mixed solution of butyl titanate and anhydrous ethanol, stir magnetically for 30 minutes to form a uniform mixed solution, place it in a polytetrafluoroethylene-lined reactor, seal it and place it in an oven for solvent thermal reaction at 220°C for 20 hours to allow butyl titanate to react on the surface of the carbon microspheres.

[0052] After the reaction, the reaction product was fully washed with deionized water and anhydrous ethanol, and dried in vacuum at 60°C for 12 h to obtain a TiO2 core-shell structure composite containing hard template carbon microspheres.

[0053] The core-shell structure composite was placed in a tube furnace, heated to 550°C at a rate of 5°C / min, and calcined in an air atmosphere for 2 hours to remove the internal hard template carbon microspheres. After cooling, hollow TiO2 microspheres were obtained.

[0054] Example 2

[0055] Weigh 0.1 g of hollow TiO2 microspheres and 0.53 g of silane coupling agent (3-mercaptopropyl)trimethoxysilane, add them into 60 mL of anhydrous ethanol / water (3:1, v:v) mixed solution, and carry out silanization grafting reaction at 65 °C with continuous stirring for 2 h.

[0056] After the reaction was completed, the mixture was dried under vacuum at 60°C for 12 h to obtain silanized hollow TiO2 microspheres.

[0057] Weigh 0.1 g of silanized hollow TiO2 microspheres, add it together with 0.32 g of photosensitizer o-phenylenediamine into 30 mL of toluene solvent and mix thoroughly, then add 3.18 g of hydrophobic crosslinker trimethylolpropane-trimethacrylate and 0.05 g of initiator 2,2′-azobis(2-methylpropionitrile), and carry out in-situ hydrothermal polymerization for 8 h at a reaction temperature of 70 °C under N2 inert atmosphere and magnetic stirring to form a three-dimensional network-like hydrophobic cross-linked polymer coating on the surface of the silanized hollow TiO2 microspheres.

[0058] After the reaction was completed, the reaction product was fully washed with anhydrous ethanol and deionized water, and vacuum dried at 60°C for 12 h to obtain a hollow TiO2-based photocatalytic composite material.

[0059] Figure 1 Field emission scanning electron microscope images of the hollow TiO2 microspheres prepared in Example 1 (a) and the hollow TiO2-based photocatalytic composite material prepared in Example 2 (b) are given. It can be seen that the hollow TiO2 microsphere product is a hollow sphere with a size of about 1 to 2 μm. After the hydrophobic cross-linked polymer layer is wrapped in an in-situ hydrothermal reaction, the product still maintains a spherical shape, but the surface becomes relatively rough, velvety, and has multiple protrusions. This is due to the incomplete uniform coating of the polymer on the surface of the hollow TiO2 microsphere, which proves the composite formation of the hollow TiO2-based photocatalytic composite material.

[0060] Figure 2 The infrared spectra (a) and X-ray diffraction spectra (b) of the hollow TiO2 microspheres in Example 1 and the hollow TiO2-based photocatalytic composite material in Example 2 are shown in the figure. -1 The strong characteristic absorption peak of Ti-O bond appeared at 1700 and 3450 cm-1 in the hollow TiO2-based photocatalytic composite material. -1 The C=O and N−H characteristic peaks from the photosensitizer o-phenylenediamine and the hydrophobic crosslinker trimethylolpropane-trimethacrylate appeared, indicating that the hydrophobic crosslinked polymer layer was coated and composited with the hollow TiO2 microspheres as expected. In addition, according to the X-ray diffraction spectrum, it can be seen that the hollow TiO2 microspheres have anatase phase (PDF No.21-1272) crystal structure, and the coating of the surface hydrophobic crosslinked polymer layer on the surface of the hollow TiO2 microspheres will not affect the crystal structure of the hollow TiO2 microspheres, so that the composite material as a whole can be excited under ultraviolet light irradiation to achieve catalytic degradation and wettability switching.

[0061] Figure 3 (a) shows the relationship between the change of the water contact angle of the hollow TiO2-based photocatalytic composite material with the change of UV irradiation time. The surface of the hollow TiO2-based photocatalytic composite material is hydrophobic at the beginning, with a water contact angle of 113° (as shown in the upper inset), proving that the hydrophobic crosslinker layer on the surface of the composite material plays a leading role at this time. After irradiation with ultraviolet light of 200-275nm for 0.5h, the water contact angle of the composite material rapidly drops to 21° (as shown in the lower inset), showing a high degree of hydrophilicity, proving that after UV irradiation, the TiO2 inside the hollow TiO2-based photocatalytic composite material is excited, releasing hydrophilic hydroxyl groups, which play a leading role through the crosslinker network, making the composite material hydrophilic.

[0062] Figure 3 (b) further shows that the surface wettability of the hollow TiO2-based photocatalytic composite material can be reversibly switched between hydrophilic and hydrophobic with repeated alternation of ultraviolet light irradiation and dark treatment, indicating that the synergistic effect of the hydrophobic outer layer of the hollow TiO2-based photocatalytic composite material and the photo-induced hydrophilic inner layer of the hollow TiO2 can achieve its surface wettability hydrophilic / hydrophobic switching under ultraviolet light / dark conditions, thereby improving the solid-liquid separation efficiency and cycle life of the composite material.

[0063] Example 3

[0064] Weigh 0.1 g of hollow TiO2 microspheres and 0.45 g of silane coupling agent (3-mercaptopropyl)trimethoxysilane, add them into 60 mL of anhydrous ethanol / water (3:1, v:v) mixed solution, and carry out silanization grafting reaction at 65 °C with continuous stirring for 2 h.

[0065] After the reaction was completed, the mixture was dried under vacuum at 60°C for 12 h to obtain silanized hollow TiO2 microspheres.

[0066] 0.1 g of silanized hollow TiO2 microspheres were weighed and added together with 0.48 g of photosensitizer o-phenylenediamine into 30 mL of toluene solvent and mixed thoroughly. Then, 2.52 g of hydrophobic crosslinker trimethylolpropane-trimethacrylate and 0.03 g of initiator 2,2′-azobis(2-methylpropionitrile) were added. Under N2 inert atmosphere and magnetic stirring conditions, the reaction temperature was controlled at 60 °C for in-situ hydrothermal polymerization for 10 h to form a three-dimensional network-like hydrophobic cross-linked polymer coating on the surface of the silanized hollow TiO2 microspheres.

[0067] After the reaction was completed, the reaction product was fully washed with anhydrous ethanol and deionized water, and vacuum dried at 60°C for 12 h to obtain a hollow TiO2-based photocatalytic composite material.

[0068] Example 4

[0069] Weigh 0.1 g of hollow TiO2 microspheres and 0.67 g of silane coupling agent (3-mercaptopropyl)trimethoxysilane, add them into 60 mL of anhydrous ethanol / water (3:1, v:v) mixed solution, and carry out silanization grafting reaction at 65 °C with continuous stirring for 2 h.

[0070] After the reaction was completed, the mixture was dried under vacuum at 60°C for 12 h to obtain silanized hollow TiO2 microspheres.

[0071] 0.1 g of silanized hollow TiO2 microspheres were weighed and added together with 0.30 g of photosensitizer o-phenylenediamine into 30 mL of toluene solvent and mixed thoroughly. Then, 5.28 g of hydrophobic crosslinker trimethylolpropane-trimethacrylate and 0.07 g of initiator 2,2′-azobis(2-methylpropionitrile) were added. Under N2 inert atmosphere and magnetic stirring conditions, the reaction temperature was controlled to 80 °C for in-situ hydrothermal polymerization for 6 h to form a three-dimensional network-like hydrophobic cross-linked polymer coating on the surface of the silanized hollow TiO2 microspheres.

[0072] After the reaction was completed, the reaction product was fully washed with anhydrous ethanol and deionized water, and vacuum dried at 60°C for 12 h to obtain a hollow TiO2-based photocatalytic composite material.

[0073] Comparative Example

[0074] No photosensitizer modification was added, and only a hydrophobic cross-linked polymer coating layer was coated on the surface of the hollow TiO2 microspheres to prepare a hollow TiO2-based photocatalytic composite material without a photosensitizer.

[0075] Weigh 0.1 g of hollow TiO2 microspheres and 0.53 g of silane coupling agent (3-mercaptopropyl)trimethoxysilane, add them into 60 mL of anhydrous ethanol / water (3:1, v:v) mixed solution, and carry out silanization grafting reaction at 65 °C with continuous stirring for 2 h.

[0076] After the reaction was completed, the mixture was dried under vacuum at 60°C for 12 h to obtain silanized hollow TiO2 microspheres.

[0077] Weigh 0.1 g of silanized hollow TiO2 microspheres, add them into 30 mL of toluene solvent and mix thoroughly, then add 3.18 g of hydrophobic crosslinker trimethylolpropane-trimethacrylate and 0.05 g of initiator 2,2′-azobis(2-methylpropionitrile), and carry out in-situ hydrothermal polymerization for 8 h at a reaction temperature of 70 °C under an inert N2 atmosphere and magnetic stirring to form a three-dimensional network-like hydrophobic cross-linked polymer coating on the surface of the silanized hollow TiO2 microspheres.

[0078] After the reaction was completed, the reaction product was fully washed with anhydrous ethanol and deionized water, and vacuum dried at 60° C. for 12 h to obtain a hollow TiO2-based photocatalytic composite material without a photosensitizer.

[0079] After testing, the hollow TiO2-based photocatalytic composite material without photosensitizer has the same anatase-type hollow TiO2 core and outer hydrophobic crosslinking agent layer as the product in the embodiment. The synergistic effect of the two makes the composite material show the same Figure 3 Consistent surface wettability with switchable capability to change UV light / dark conditions.

[0080] Application Examples

[0081] Hollow TiO2 microspheres were prepared according to Example 1, hollow TiO2-based photocatalytic composite materials were prepared according to Example 2, and hollow TiO2-based photocatalytic composite materials without photosensitizer were prepared according to the comparative example, which were used to degrade Rhodamine B in aqueous solution.

[0082] Specifically, 20 mL of a 10 mg / L Rhodamine B aqueous solution was measured, and 10 mg of each of the above photocatalytic materials was added respectively. The relationship between the degree of catalytic degradation of the solution and time (0.5, 1, 2, 3, 4 h) was measured by an ultraviolet spectrophotometer.

[0083] After the degradation is completed, the surface of the photocatalytic material is made hydrophobic by dark placement, so that it can be easily separated and recovered from the solution by centrifugal separation, and then used again for the degradation of Rhodamine B in aqueous solution after drying.

[0084] Figure 4 The following is the change of the ultraviolet absorbance of the aqueous solution over time during the degradation of Rhodamine B by the hollow TiO2-based photocatalytic composite material in Example 2 (a) and the degradation curve (b). On the absorbance spectrum of (a), the absorbance peak near the wavelength of 550nm is the characteristic peak of Rhodamine B in the aqueous solution. It can be seen that in the first 0.5h, the characteristic peak of Rhodamine B decreases most significantly, and as the degradation time increases, the height of the characteristic peak continues to decrease. Further quantitative analysis of the Rhodamine B degradation curve shown in (b) shows that within the first 0.5h, Rhodamine B is rapidly degraded, and the degradation rate can reach 80%; as the degradation time continues to increase, at 4h of degradation, the degradation rate of Rhodamine B can reach 92%, indicating the high efficiency degradation ability of the hollow TiO2-based photocatalytic composite material of Example 2 for Rhodamine B.

[0085] Figure 5 The regeneration performance of the hollow TiO2-based photocatalytic composite material in Example 2 for degrading Rhodamine B is shown. It can be seen that the degradation rate reaches 92% when the hollow TiO2-based photocatalytic composite material is used to degrade Rhodamine B for the first time. After the degradation is completed, the surface of the composite material is made hydrophobic by dark placement. After centrifugal separation and drying and recovery, the degradation rate can remain unchanged when it is used for the degradation of Rhodamine B in aqueous solution for the second time. Repeating the recycling process, the degradation rate of the composite material for Rhodamine B in the fifth use can still reach 90%, which is 97.8% of the degradation rate of the first use, indicating that the hollow TiO2-based photocatalytic composite material has a switchable wettability surface, which promotes the separation and regeneration of the material and has a good cycle life.

[0086] The catalytic degradation effect and recycling status of the hollow TiO2-based photocatalytic composite materials of the products of Example 3 and Example 4 on Rhodamine B were tested in the same manner, and the test results were consistent with those of the product of Example 2.

[0087] Figure 6 This is the case where the hollow TiO2 microspheres in Example 1 are directly used as photocatalysts for the degradation of Rhodamine B. From the curve of the ultraviolet absorbance of the aqueous solution (a) over time, it can be seen that the characteristic peak of Rhodamine B near a wavelength of 550nm continues to decrease with the increase of degradation time, but the decrease is limited. Furthermore, through quantitative analysis of the degradation curve (b), it can be seen that Rhodamine B is rapidly degraded in the first 0.5 and 1h, with a degradation rate of 46%; as the degradation time continues to increase, the degradation rate of Rhodamine B at 4h is only 48%. Comparison Figure 4 Example 2 shows the degradation of Rhodamine B by the hollow TiO2-based photocatalytic composite material. It can be seen that due to the lack of modification by the photosensitizer, the ability of the hollow TiO2 microspheres to catalyze the degradation of Rhodamine B is significantly lower than that of the hollow TiO2-based photocatalytic composite material.

[0088] Figure 7 The regeneration performance of the hollow TiO2 microspheres in Example 1 for degradation of Rhodamine B was compared. The degradation rate was only 48% when it was first used to degrade Rhodamine B, and the surface of the hollow TiO2 microspheres without a composite hydrophobic crosslinker was always hydrophilic, requiring more time-consuming multiple centrifugal separations to be fully recovered, and then used again for the degradation of Rhodamine B in aqueous solution after drying. Repeating the recycling process, the degradation rate of the hollow TiO2 microspheres put into use for the fifth time has dropped to 30% for Rhodamine B, which is only 62.5% of the degradation rate of the first use, which is significantly lower than the degradation rate maintenance of the hollow TiO2-based photocatalytic composite material in Example 2 when it was recycled for the fifth time (97.8%), indicating that the hollow TiO2 microspheres without surface modification and coating composites do not have a surface with switchable wettability, which is not conducive to the separation and regeneration of the material, resulting in a poor cycle life of the material.

[0089] The above comparison shows that by modifying the photosensitizer o-phenylenediamine on the surface of the hollow TiO2 microspheres and coating them with a hydrophobic crosslinker polymer layer for composite, the catalytic activity, catalytic efficiency and cycle life of the photocatalytic material can be significantly improved.

[0090] Figure 8 The following are the changes in the ultraviolet absorbance of the aqueous solution during the degradation of Rhodamine B by the hollow TiO2-based photocatalytic composite material without photosensitizer (a) and the degradation curve (b). It can be seen from the ultraviolet absorbance change graph (a) that the height of the characteristic peak of Rhodamine B near the wavelength of 550nm also decreases with the increase of degradation time. Further quantitative analysis of the Rhodamine B degradation curve (b) shows that the composite material prepared in the comparative example does not contain the photosensitizer o-phenylenediamine, and its final degradation rate of Rhodamine B is only 46%, which is consistent with the degradation rate of the hollow TiO2 microspheres in Example 1, and is lower than the hollow TiO2-based photocatalytic composite material containing o-phenylenediamine photosensitizer in the example.

[0091] In addition, different from the degradation curve trends of Example 1 and Example 2, the degradation curve of the comparative product when degrading Rhodamine B under the same conditions was obviously relatively gentle, and the degradation was not quickly completed within 1 hour. The reason is that on the one hand, the surface hydrophobic cross-linking agent coating slightly hindered the absorption of ultraviolet light by the hollow TiO2 microspheres, and on the other hand, the lack of photosensitizer to promote the separation and transmission efficiency of photogenerated carriers failed to improve the degradation efficiency.

[0092] It can be seen that photosensitizer plays an important role in the hollow TiO2-based photocatalytic composite material system.

[0093] The above embodiments of the present invention do not describe all the details in detail, nor limit the present invention to the above embodiments. Various changes, modifications, substitutions and variations made by ordinary technicians in this field without departing from the principles and purpose of the present invention should be included in the protection scope of the present invention.

Claims

1. A hollow TiO2-based photocatalytic composite material for degrading rhodamine B, which is prepared by using anatase-type hollow TiO2 microspheres as a catalytic matrix, modifying an aniline compound photosensitizer on the surface, and coating a hydrophobic crosslinker polymer layer formed by using an acrylate hydrophobic crosslinker as a raw material.

2. The method for preparing the hollow TiO2-based photocatalytic composite material for degrading rhodamine B as described in claim 1 is to obtain silanized hollow TiO2 microspheres after silanization modification of anatase-type hollow TiO2 microspheres with a silane coupling agent, add aniline compound photosensitizer, acrylate hydrophobic crosslinking agent and initiator in a toluene solvent system, and perform in-situ hydrothermal reaction under an inert atmosphere to form a three-dimensional network-like hydrophobic crosslinked polymer layer coated on the surface of the hollow TiO2 microspheres to obtain the hollow TiO2-based photocatalytic composite material.

3. The preparation method according to claim 2, characterized in that The anatase hollow TiO2 microspheres are obtained by using carbon microspheres prepared by hydrothermal method as hard templates, using butyl titanate to carry out solvent thermal self-assembly reaction on the surface of carbon microspheres, and calcining at high temperature in air atmosphere to remove the internal hard template carbon microspheres.

4. The preparation method according to claim 2, characterized in that The silane coupling agent is (3-mercaptopropyl) trimethoxysilane, and the dosage is 4 to 8 times the mass of the hollow TiO2 microspheres.

5. The preparation method according to claim 2, characterized in that The aniline compound photosensitizer is o-phenylenediamine, and the dosage is 3 to 5 times the mass of the silanized hollow TiO2 microspheres.

6. The preparation method according to claim 2, characterized in that The acrylate hydrophobic crosslinking agent is trimethylolpropane-trimethacrylate, and the amount used is 20 to 55 times the mass of the silanized hollow TiO2 microspheres.

7. The preparation method according to claim 2, characterized in that The initiator is a low-activity azo initiator or an inorganic persulfate initiator.

8. The preparation method according to claim 2, characterized in that The initiator is 2,2'-azobis(2-methylpropionitrile), and the amount used is 0.3 to 0.7 times the mass of the silylated hollow TiO2.

9. The preparation method according to claim 2, characterized in that The in-situ hydrothermal reaction temperature is 60-80° C., and the reaction time is 6-14 hours.

10. Use of the hollow TiO2-based photocatalytic composite material according to claim 1 in catalytic degradation of Rhodamine B in water.

Citation Information

Patent Citations

  • Preparation method of titanium dioxide based composite photocatalyst with visible-light response function

    CN103861649A

  • PANI (polyaniline)-modified N-doped TiO2 (titanium dioxide) composite photocatalyst adopting nanostructure as well as preparation method and application of photocatalyst

    CN104857995A

  • Compound catalyst as well as preparation method and application thereof

    CN109513465A

  • Preparation of high-efficiency TiO2 photocatalyst and application of high-efficiency TiO2 photocatalyst in degradation of water pollutants

    CN111468090A

  • Hydrophilic / hydrophobic ultraviolet response switchable carbon-based phenol imprinting adsorption material and preparation method thereof

    CN113042012A